Disharmony of Regional Regulation Number 27 of 2004 in Relation to Law Number 12 of 2011 - Veri Ananda Putri Laili Rohmatillah; Fatimatus Zahro; Lovika Augusta (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to analyze the disharmony of Regional Regulations (Perda) with higher legislative regulations and to seek solutions to address these issues. The research method used is normative legal research with an approach to analyzing legislative regulations. The results indicate that the disharmony of Perda with legislative regulations can lead to legal conflicts, legal uncertainty, and detriment to society. Therefore, it is necessary to harmonize Perda with higher legislative regulations through the evaluation and revision of incompatible Perda. This study recommends that local governments pay attention to the hierarchy of legislative regulations in the formulation of Perda and enhance the capacity and knowledge of local government officials in the field of law.